Effect of Resveratrol on Blood Rheological Properties in LPS-Challenged Rats - Wang, Ying; Cui, Hao; Niu, Fei; Liu, Shuo-Lin; Li, Yao; Zhang, Li-Min; Du, Hui-Bo; Zhao, Zi-Gang; Niu, Chun-Yu (Frontiers in Physiology, 2018)
Objectives: Abnormal rheological properties induce adverse effects during sepsis. This study sought to investigate the hypothesis that (Res) improves blood rheological properties in rats following a lipopolysaccharide (LPS) challenge, and provide a novel approach for treatment of sepsis. Methods: The rats were intraperitoneally or intramuscularly injected with vehicle, LPS (8 mg/kg), Res (30 mg/kg) or both to yield four groups: control, Res, LPS, and LPS+Res. After 6 h of LPS and/or Res injection, the mean arterial pressure (MAP), regional blood flow, erythrocyte and leukocyte parameters, and blood viscosity were observed. Results: LPS administration had no significant effects on the erythrocyte parameters and plasma viscosity. LPS administration reduced the MAP, whole blood viscosity at low and medium shear rates, the blood flow in the spleen and kidney, and the leukocyte content in whole blood when compared to control group, and increased the myeloperoxidase (MPO) activity in lung. Treatment with Res alone had no effects on most of parameters observed except increasing the whole blood relative viscosity. However, Res treatment after LPS resulted in further decrease in whole blood viscosity at high and medium shear rates. Furthermore, Res treatment conversely decreased the red blood cell distribution width-CV, blood flow of stomach, whole blood relative viscosity and MPO activity in lung, and increased the leukocyte content, but did not restore LPS-induced decrease in MAP and the blood flow in the spleen and kidney. Conclusion: The Res treatment partly reduce the whole blood viscosity and regional blood flow, and increase WBC content in peripheral blood following the LPS challenge, suggesting a favorable role in expanding the quasi-sympathetic effects of LPS in blood viscosity at early stages.